Administrative Empowerment Impact on Enhancing the Leadership Skills for Modern Environment of Judiciary - Ahmed Abo Eisheh; Moza Al-Ghaithi; Faris M. AL-Oqla (Ital Publication, 2023)
Administrative empowerment aims to enhance teamwork spirit and expand the scope of supervision by giving workers the necessary powers and ability to make decisions towards sustainable management and decentralization. This study aims to determine the effect of the administrative empowerment context on developing the leadership skills of the second-level leaders in the Council of Administrative Affairs for the Judiciary in the Sultanate of Oman towards a more sustainable modern environment in this sector. Analysis of variances (ANOVA) method was utilized to investigate the effect of several related factors, including delegation of authority, task forces, effective communication, and training. Results have revealed that the current level of administrative empowerment was found medium in the council. However, the level of leadership skills of the second-level leaders was found to be high, but with insignificant utilization. It was also found that there were statistically significant effects for all the dimensions of administrative empowerment on developing the leadership skills of the second-level leaders. The novel results of the impact of delegation of authority on the environment of the judiciary in Oman have several consequences in the field. It can practically change the delegation of authority in the council to enhance administrative empowerment and the skill development of second-level leaders in the judiciary sector. Doi: 10.28991/ESJ-2023-07-05-013 Full Text: PDF